COPD Guidelines: Old Gold versus New Gold - Ahasan, HAM Nazmul; Hossain, Homayra Tahseen (Bangladesh Journal of Medicine, 2018)
Chronic Obstructive Pulmonary Disease (COPD) is a major cause of chronic morbidity and mortality throughout the world. The Global Initiative for Chronic Obstructive Lung Disease (GOLD) is an international committee of experts who periodically update the knowledge on the diagnosis and management of COPD since 2001. This year 2017, the GOLD initiative published the 5-year update on the diagnosis and management of COPD.This review article mainly highlights the differences between old GOLD versus new GOLD guideline. Compared to the previous version, this documents has been an extensively revised: the definition has been simplified, highlighting the importance of respiratory symptoms, and disease development is further discussed, including new insights on lung development. Spirometry is no longer included in the ABCD tool, which is now centered exclusively on respiratory symptoms and history of exacerbation. Subsequently, pharmacologic treatment has been shifted towards a more personalized approach. For the first time, GOLD proposes escalation strategies. Preference is given to LABA/LAMA (long-acting beta-agonist/long-acting muscarinic antagonists) combinations over LABA/ICS (long-acting beta-agonist/inhaled corticosteroid) combinations as a mainstay of treatment. Bangladesh J Medicine Jan 2018; 29(1) : 31-35